Empirical perspectives on approaches to teach life cycle assessment in higher education - Kai Rüdele; Verena Schnaitter; Tobias Viere; Sanni Väisänen; Matthias Wolf (Discover Sustainability)
Abstract A comprehensive understanding of ecological impacts is paramount for preparing a generation of informed and environmentally conscious problem-solvers. Higher education institutions recognize their role as contributors to environmental literacy and competencies necessary for prompting a sustainable clean environment. Life cycle assessments (LCA) provide one channel for students to understand and quantify the consequences of production and consumption. This study explores the current teaching approaches together with learning objectives and disciplinary contexts of LCA courses taught at universities, highlighting their global expansion and interdisciplinary relevance. Employing a mixed-methods approach, including a systematic literature review, curriculum analysis of the current course landscape at European universities, and a global survey among lecturers, the research identifies key trends in LCA education. Particular attention is paid to how LCA education is conducted and whether students are confronted with the same challenges as practitioners. Findings from empirical data emphasize the growing adoption of active learning methods, such as case studies and project-based collaborations, alongside traditional lectures. It has become apparent that instructors are already striving to enhance the LCA methodology with practical engagement. Despite notable progress, challenges persist, including the need for standardization and alignment with industry expectations. Moreover, this study provides a foundation for advancing LCA didactics through more effective approaches.